Clarification of Terminologia Embryologica: Gartner Duct (International Journal of Medical and Surgical Sciences, 2015)
The use of eponyms is still a practice used among clinical, despite the efforts of the morphological community uprooting of medical language. The reason of this study is to make a clarification regarding Terminology Embryologica Gartner duct, mesonephric duct derived structure present in women and gynecobstetric great interest because of their potential pathological complications. We propose amendments with respect to derivatives mesonephric duct and its name.